Differential Responses of the Septal Ventricle and the Atrial Signals During Ongoing Entrainment: A Method to Differentiate Orthodromic Reciprocating Tachycardia Using Septal Accessory Pathways From Atypical Atrioventricular Nodal Reentry. (October 2015) - Calvo, David; Ávila, Pablo; García-Fernández, F. Javier; Pachón, Marta; Bravo, Loreto; Eidelman, Gabriel; Hernández, Jesús; Miracle, Ángel L.; Rubín, José; Pérez, Diego; Arenal, Ángel; Atienza, Felipe; et al.
Abstract : Background—: Differential diagnosis between tachycardia mediated by septal accessory pathways (AP) and atypical atrioventricular nodal reentry can be challenging. We hypothesized that an immediate versus delayed pace-related advancement of the atrial electrogram, once the local septal parahisian ventricular electrogram (SVE) has been advanced, may help in this diagnosis. Methods and Results—: We focused on differential timing between SVE and atrial signals at the initiation of continuous right ventricular apical pacing during tachycardia. SVE advancement preceding atrial reset was defined as SVE advanced by the paced wave fronts while atrial signal continued at the tachycardia cycle. We analyzed 51 atypical atrioventricular nodal reentry (45% posterior type) and 80 AP tachycardias (anteroseptal [10], parahisian [18], midseptal [12], and posteroseptal [40]). SVE advancement preceding atrial reset was observed in 98% of atrioventricular nodal reentries during 4±1.1 cycles; this phenomena was observed in 6 (8%) of the atrioventricular reentrant tachycardia mediated by septal AP ( P <0.001; sensitivity 98%; specificity 93%; positive predictive value 90%; negative predictive value 99%) and lasted 1 single cycle ( P <0.001). Right posteroseptal AP tachycardias were distinctly characterized by atrial reset preceding SVE advancement (with ventricular fusion; specificity 100%; positive predictive value 100%). In 11 cases, it was impossible to achieve sustain entrainment. In all of them, the differential responses at the entrainment attempt allowed for appropriate diagnosis. Conclusions—: The differential response of the SVE and the atrial electrogram at the initiation of continuous right ventricular apical pacing during tachycardia effectively distinguishes between atypical atrioventricular nodal reentry and atrioventricular reentrant tachycardia mediated by septal APs.